Fast Virtual Garment Dressing on Posed Human Model (Journal of Fiber Bioengineering and Informatics, 2018)
Due to the multiplicity of the implementation, virtual garment simulation requires thecapacity of dressing a sewn garment onto various posed human models in a real time. In this paper, athree-step method has been proposed to accelerate the dress-up procedure. The virtual garment is firstdressed onto a human model in a standing pose to record a distance map between the garment shell andthe human model. And then the distance map is employed to generate a coarse match when the pose ofthe human model has been changed. Finally, a fine-tuned 3D configuration without surface penetrationis generated after a draping/relaxation scheme. Experimental results suggest this method is a useful andfast treatment for dressing sewn virtual garment on various posed human models.
Keywords: virtual garment; distance map; mesh conforming; draping; global relaxation